2005
DOI: 10.1111/j.1600-0501.2005.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soft tissue around single‐tooth implant crowns: the pink esthetic score

Abstract: The PES reproducibly evaluates peri-implant soft tissue around single-tooth implants. Thus, an objective outcome of different surgical or prosthodontic protocols can be assessed. Orthodontists were clearly more critical than the other observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
902
3
27

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 731 publications
(987 citation statements)
references
References 10 publications
17
902
3
27
Order By: Relevance
“…Il convient donc dès la pose de l'implant d'évaluer ce biotype et de réaliser, en cas de biotype fin, une greffe de conjonctif enfoui. La qualité du biotype initialement devra être comparée à celle obtenue en fin de traitement afin de déterminer le niveau de succès esthétique de la réhabilitation « Pink Esthetic Score » [13].…”
Section: Le Biotype Parodontalunclassified
“…Il convient donc dès la pose de l'implant d'évaluer ce biotype et de réaliser, en cas de biotype fin, une greffe de conjonctif enfoui. La qualité du biotype initialement devra être comparée à celle obtenue en fin de traitement afin de déterminer le niveau de succès esthétique de la réhabilitation « Pink Esthetic Score » [13].…”
Section: Le Biotype Parodontalunclassified
“…It has been demonstrated that over 60% of cases showed a colour mismatch between single implant restoration and natural tooth gingiva [11]. After gingiva recession, the titanium implant becomes exposed [11,12]. Moreover, the release of metal ions could induce discolouration of gingiva after implantation in a slow and continuous way, leading to dissatisfaction with the long-term aesthetic results.…”
Section: Introductionmentioning
confidence: 99%
“…The metallic colour cannot be fully hidden by the soft tissue peri-implant, which induces a greyish appearance, especially for patients with thin soft tissue [8][9][10]. It has been demonstrated that over 60% of cases showed a colour mismatch between single implant restoration and natural tooth gingiva [11]. After gingiva recession, the titanium implant becomes exposed [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes autores han intentado establecer un método válido (usando diferentes parámetros). A criterio del taller ninguno abarca todas las posibles variables que en la determinación de éxito se pueden considerar (42,43) . A pesar de lo expuesto se eligió al índice de Belser, como el más completo en los criterios de evaluación ya que tiene la ventaja de evaluar tanto los tejidos blandos: Pink Esthetic Score (PES) como la restauración: White Eshetic Score (WES).…”
unclassified
“…Different authors have tried to develop a valid method (using different parameters). In the opinion of the workshop participants, none covers all the variables that can be considered to measure success (42,43) . Despite this, the Belser index was chosen as the most complete one in terms of evaluation criteria, since it evaluates both soft tissues: Pink Esthetic Score (PES) and the restoration: White Esthetic Score (WES).…”
mentioning
confidence: 99%